2021
DOI: 10.1038/s41598-020-79628-w
|View full text |Cite
|
Sign up to set email alerts
|

Performance and application analysis of ANFIS artificial intelligence for pressure prediction of nanofluid convective flow in a heated pipe

Abstract: Heat transfer augmentation of the nanofluids is still an attractive concept for researchers due to rising demands for designing efficient heat transfer fluids. However, the pressure loss arisen from the suspension of nanoparticles in liquid is known as a drawback for developing such novel fluids. Therefore, prediction of the nanofluid pressure, especially in internal flows, has been focused on studies. Computational fluid dynamics (CFD) is a commonly used approach for such a prediction of fluid flow. The CFD t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The use of CFD techniques in artificial intelligence has gained attention in the last few years. An adaptive network-based fuzzy inference system (ANFIS) was also credited with the contribution of artificial intelligence to CFD in a few types of research 22 28 . The results released the efficiency of the ANFIS for the accurate predictions of the CFD results.…”
Section: Introductionmentioning
confidence: 99%
“…The use of CFD techniques in artificial intelligence has gained attention in the last few years. An adaptive network-based fuzzy inference system (ANFIS) was also credited with the contribution of artificial intelligence to CFD in a few types of research 22 28 . The results released the efficiency of the ANFIS for the accurate predictions of the CFD results.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of scientific works are devoted to this direction. So, in [1], the authors present the research results regarding the application of fuzzy inference system (ANFIS) to control the heat transfer augmentation of the nanofluids. In this paper, the authors have demonstrated the performance of the artificial intelligence algorithm as an auxiliary method for cooperation with the computational field dynamic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are four main types of methods for capacity forecasting. The first is the method based on statistical analysis [6][7][8][9], which uses historical data and techniques such as trend analysis to predict future capacity through data analysis and modelling. It typically requires a substantial amount of high-quality data, making it unsuitable for early capacity assessments, especially in scenarios with limited data.…”
Section: Introductionmentioning
confidence: 99%